m-Polar Quadripartitioned Neutrosophic Graphs with Applications in Decision-Making for Mobile Network Selection - Basavaraj V Hiremath; Durga Nagarajan; Satham Hussain S; Hossein Rashmanlou; Farshid Mofidnakhaei (Neutrosophic Sets and Systems)
In today’s rapidly evolving world, the shift towards multi-polarity is increasingly evident, significantly influencing various scientific and technological domains, particularly in information and data sciences. This study introduces m-polar Quadripartitioned neutrosophic sets and graphs, along with key results and operations, such as the composition and Cartesian product of m-polar quadripartitoned neutrosophic graphs, supported by illustrative examples to clarify the proposed concepts. Additionally, recognizing the complexity of selecting a mobile network shaped by factors like coverage, data speed, pricing, and customer service-we propose a novel decision-making approach using a score function within the framework of m-polar quadripartitioned neutrosophic sets. This methodology enables users to evaluate and compare multiple mobile networks effectively across various criteria.